NAR-DOS ON THE MEANING OF LIFE - MIRZOYAN, VALERI (Bulletin of Yerevan University E: Philosophy, Psychology, 2019)
The article discusses the questions about the meaning of life and death in works of outstanding Armenian writer Nar-Dos. The emphasis is on the detailed analysis of one of the fundamental works by Nar-Dos, the novel "The Death". The attitude of Nar-Dos towards the people with the pessimistic orientation to life is shown here. Though the novels of the Armenian writer were published more than 100 years ago, his characters, the multifaceted reality of human life, the solutions proposed by the author are quite topical and provide a rich source of thought to the present generation.